Blood pressure-lowering effect of repeated Waon therapy in non-smokers with hypertension. Issue 23 (11th June 2021) - Kominami, Kazuyuki; Takahiza, Etsuko; Tabuchi, Mineko; Akino, Masatoshi
Abstract : Abstract: Waon therapy (WT) has been used as a thermal therapy in chronic heart failure patients. However, its effect in patients with hypertension is unclear. This study aimed to reveal the hypotensive effect of WT in patients with hypertension. WT was performed on 31 patients with hypertension (63.9 ± 11.9 years, male: 17) on standard hypertension treatment focusing on lifestyle modification and medication. Systolic and diastolic blood pressures were measured before and after WT using an upper arm automated sphygmomanometer. We investigated the effect of single and repeated (1 time/d, >5 times) WT sessions on blood pressure and further compared its effect between current smoking (n = 11, 55.4 ± 6.4 years, 8.5 ± 2.4 times) and non-smoking (n = 11, 66.9 ± 8.5 years, 12.2 ± 5.9 times) groups. A total of 370 sessions of WT were conducted. Systolic and diastolic blood pressures significantly decreased after a single WT session (systolic blood pressure: 118.5 ± 10.1 to 115.1 ± 9.0 mm Hg, P  < .001; diastolic blood pressure: 70.5 ± 6.4 to 65.9 ± 5.3 mm Hg, P  < .001). The blood pressure decrease following repeated WT was not significant when all participants were considered (systolic blood pressure: 122.3 ± 15.2 to 116.9 ± 19.6 mm Hg; diastolic blood pressure: 73.8 ± 16.7 to 68.2 ± 13.2 mm Hg); however, it was significant in the non-smoking group (systolic blood pressure: 124.2 ± 11.3 to 108.8 ± 13.4 mm Hg, P  < .001; diastolic blood pressure: 73.6 ± 4.9 to 62.1 ± 7.6 mm Hg, P  < .001). Repeated WT (at least 5 sessions) decreased blood pressure in patients with hypertension, especially in non-smokers. WT is a simple method to reduce blood pressure in non-smoking patients with hypertension. Abstract : Supplemental Digital Content is available in the text